1999
DOI: 10.1590/s1516-89131999000400006
|View full text |Cite
|
Sign up to set email alerts
|

Pollination ecology of Swartzia apetala Raddi var. apetala (leguminosae-papilionoideae)

Abstract: The pollination ecology of Swartzia apetala Raddi var. apetala was studied in the restinga of Maricá, State of Rio de Janeiro, Brazil. S. apetala var. apetala is a shrub with asynchronic annual blooming, between the months of November and April (hot-rainy season). Each plant can exhibit more than one blooming episode in this period. Their flowers are hermaphrodites, apetalous, heterantherous, odoriferous, and the pollen represents the only reward offered to visitors. It is pollinized by species of Centris and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
5
10
0
2
Order By: Relevance
“…This kind of floral morphology can thus limit the spectrum of visitors able to forage on flowers and may work as a strategy for effective pollination. Pollen deposition on different areas of the pollinator's body in the studied Senna and Swartzia species is a result of heteranthery, an attribute already recorded for other Swartzia species (Lopes & Machado 1996;Moço & Pinheiro 1999), in various genera of the tribe Cassiinae (Dulberger 1981;Gottsberger & Silberbauer-Gottsberger 1988;Westerkamp 2004) and in at least 20 families (Endress 1994;Vallejo-Marín et al 2010). Heteranthery, resulting in functional separation of pollen for feeding and pollen for pollination, has been considered an evolutionary response to assure pollination while feeding voracious foraging bees (Vogel 1978;Buchmann 1983;Luo et al 2008;Vallejo-Marín et al 2009;Papaj et al 2017).…”
Section: Floral Phenology Morphology and Biologysupporting
confidence: 64%
See 3 more Smart Citations
“…This kind of floral morphology can thus limit the spectrum of visitors able to forage on flowers and may work as a strategy for effective pollination. Pollen deposition on different areas of the pollinator's body in the studied Senna and Swartzia species is a result of heteranthery, an attribute already recorded for other Swartzia species (Lopes & Machado 1996;Moço & Pinheiro 1999), in various genera of the tribe Cassiinae (Dulberger 1981;Gottsberger & Silberbauer-Gottsberger 1988;Westerkamp 2004) and in at least 20 families (Endress 1994;Vallejo-Marín et al 2010). Heteranthery, resulting in functional separation of pollen for feeding and pollen for pollination, has been considered an evolutionary response to assure pollination while feeding voracious foraging bees (Vogel 1978;Buchmann 1983;Luo et al 2008;Vallejo-Marín et al 2009;Papaj et al 2017).…”
Section: Floral Phenology Morphology and Biologysupporting
confidence: 64%
“…The medium to large-sized bees observed in this study have been reported as pollinators of several other legume species with medium and large-sized flowers: Euglossina species are the main pollinators of Swartzia pickelli (Lopes & Machado 1996), and Xylocopa and Centridini bees of Swartzia apetala (Moço & Pinheiro 1999) and of several Senna species (Carvalho & Oliveira 2003), as well as several Cassiinae species with pollen flowers (Dulberger 1981;Gottsberger & Silberbauer-Gottsberger 1988). These cohorts of buzz-collectors have also been reported as pollinators of several Caesalpinioideae with nectar flowers (Cocucci et al 1992;Lewis & Gibbs 1999), and most of them are important pollinators of many canopy tree species of Neotropical forests Bawa 1985a;1990).…”
Section: Floral Visitorssupporting
confidence: 52%
See 2 more Smart Citations
“…Essas mesmas características estão presentes em grãos de pólen de fl ores com deiscência poricida (Silva et al 2002) ou com deiscência rimosa (Moço & Pinheiro 1999), que dependem da vibração dos estames a fi m de que o pólen seja transferido das anteras para o polinizador.…”
Section: Discussionunclassified